Unemployment Fluctuations in the United States: Further Tests of the Sectoral-Shifts Hypothesis - Mills, Terence C.; Pelloni, Gianluigi; Zervoyianni, Athina (The Review of Economics and Statistics, 1995)
Terence C. Mills, Gianluigi Pelloni, Athina Zervoyianni, Unemployment Fluctuations in the United States: Further Tests of the Sectoral-Shifts Hypothesis, The Review of Economics and Statistics, Vol. 77, No. 2 (May, 1995), pp. 294-304